Risk factors for erectile dysfunction in patients with cardiovascular disease - Chaudhary, Rakesh Kumar (J Int Med Res, 2016)
OBJECTIVE: To examine the relationship between risk factors for cardiac disease and erectile dysfunction (ED) in men from Xi’an, China. METHODS: Participants were patients with cardiovascular disease who visited the Cardiovascular Medicine Department of Xi’an Jiaotong University First Affiliated Hospital between September 2011 and March 2012. Two hundred and fifty patients were issued with questionnaires and underwent a physical examination and blood test.Risk factors for ED were identified using univariate and multivariate analyses. RESULTS: In total, 222 participants returned valid questionnaires (89% response rate), underwent a physical examination and blood test, and were included in the study. The most common cardiovascular diseases were hypertension (n = 142; 64%), coronary heart disease (n = 90; 41%) and angina pectoris (n = 78; 35%). Most patients (n = 144; 65%) had two or more cardiovascular diseases. Age, smoking, body mass index, total cholesterol level, hypertension and the ratio of total cholesterol to high-density lipoprotein cholesterol were significantly associated with ED. Domestic location, level of education, participation in physical activity, diabetes and drinking alcohol were not associated with ED. CONCLUSIONS: Common risk factors for cardiovascular disease are associated with ED in patients with cardiovascular disease. This study furthers understanding of the risk factors for ED in Chinese patients with cardiovascular disease and paves the way for further research into the prevention of ED.